If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3 + m) = 8(6m + 7) (3 * 4 + m * 4) = 8(6m + 7) (12 + 4m) = 8(6m + 7) Reorder the terms: 12 + 4m = 8(7 + 6m) 12 + 4m = (7 * 8 + 6m * 8) 12 + 4m = (56 + 48m) Solving 12 + 4m = 56 + 48m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-48m' to each side of the equation. 12 + 4m + -48m = 56 + 48m + -48m Combine like terms: 4m + -48m = -44m 12 + -44m = 56 + 48m + -48m Combine like terms: 48m + -48m = 0 12 + -44m = 56 + 0 12 + -44m = 56 Add '-12' to each side of the equation. 12 + -12 + -44m = 56 + -12 Combine like terms: 12 + -12 = 0 0 + -44m = 56 + -12 -44m = 56 + -12 Combine like terms: 56 + -12 = 44 -44m = 44 Divide each side by '-44'. m = -1 Simplifying m = -1
| (x+9i)(x-9i)=0 | | 4x+7=22-x | | 7z-1=z+22 | | 3v+2y=100 | | 6cosx=4sinx | | (-x-9i)(x+9i)=0 | | -5x-1=29+5x | | -4y+7x=-24 | | 7x-(3+4x)= | | 3a-15=-14 | | 3c+18=14 | | 3r^2+25r+8=0 | | 14x-29=6x+29 | | C=.15M+15 | | 57+66+x=180 | | 1/8logx=-5/3 | | 13-2x=93 | | -5(3x-9)=150 | | 66+x+x=180 | | 1/2X-10=6 | | y^2-8y=20 | | 9x-2=98 | | (-4i)(2i)(-3i)= | | 6/5÷5/8 | | 7(d+2)=2(d-7)+5d | | 2X+Y=356 | | 7xy*9=0 | | -6x+4=-41+3x | | -3p+8=14 | | 3-1/8=9/2 | | x^2-Y^2=63 | | 3x-2=7-2 |